1996
DOI: 10.1038/bjc.1996.340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of p53 overexpression and mutation in colorectal adenocarcinomas

Abstract: Summary The p53 tumour-suppressor gene is found altered in the majority of colorectal cancers. Lesions include allelic loss, mutation of the gene and overexpression of the p53 protein. All of these lesions have been analysed for prognostic significance, and whereas both mutation and allelic loss have been shown to be reasonably useful markers of prognosis, the utility of overexpression of the p53 protein is more ambiguous.Given that many authors use p53 overexpression as a marker for point mutation this issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 54 publications
2
42
0
2
Order By: Relevance
“…In colorectal carcinoma, various studies have reported that: p53 mutations are associated with short survival (Hamelin et al, 1994;Goh et al, 1995), over expression of the p53 protein is a useful prognostic indicator (Auvinen et al, 1994), and that positive p53 immunostaining is associated with poor overall survival (Lanza et al, 1996). Where these observations have been made in some studies, such correlations have not been observed in other studies (Bell et al, 1993;Morrin et al, 1994;Mulder et al, 1995;Smith et al, 1996). Accordingly, the prognostic value of p53 mutations in colorectal carcinogenesis is controversial.…”
mentioning
confidence: 72%
“…In colorectal carcinoma, various studies have reported that: p53 mutations are associated with short survival (Hamelin et al, 1994;Goh et al, 1995), over expression of the p53 protein is a useful prognostic indicator (Auvinen et al, 1994), and that positive p53 immunostaining is associated with poor overall survival (Lanza et al, 1996). Where these observations have been made in some studies, such correlations have not been observed in other studies (Bell et al, 1993;Morrin et al, 1994;Mulder et al, 1995;Smith et al, 1996). Accordingly, the prognostic value of p53 mutations in colorectal carcinogenesis is controversial.…”
mentioning
confidence: 72%
“…11 Due to the reasons cited above, it is no wonder that most researches found a relative weak concordance of both techniques, ranging from 53-74%. 21,40 The report by Smith et al, 22 describing a strong association of detectable levels of immunoreactive p53 and DNA mutations using the antibody Pab 240, represented only a rare case. 22 In our study, we persisted in the use of ICC for the determination of p53 status because we noted that ICC using p53 DO.1 antibody was technically highly reproducible and its result was highly concordant with that of genomic analysis, based on our previous sound studies.…”
Section: Discussionmentioning
confidence: 99%
“…21,40 The report by Smith et al, 22 describing a strong association of detectable levels of immunoreactive p53 and DNA mutations using the antibody Pab 240, represented only a rare case. 22 In our study, we persisted in the use of ICC for the determination of p53 status because we noted that ICC using p53 DO.1 antibody was technically highly reproducible and its result was highly concordant with that of genomic analysis, based on our previous sound studies. 20,54 Moreover, although direct genomic analyses are theoretically more precise, they are less practical and cumbersome if used on a large scale in the day-to-day management of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on identical tumor sets of colorectal carcinoma samples, concordant results between IHC and single strand conformation polymorphism (SSCP) ranged between 53% and 71%. 36,37 Furthermore, Greenblatt et al 38 FIGURE 2. Kaplan-Meier curves for cumulative disease free survival in 100 patients with rectal carcinoma according to p53 status: immunopositive, Ն5% nuclei stained (n ϭ 55); immunonegative, Ͻ5% nuclei stained (n ϭ 45) (P ϭ 0.18, log rank test).…”
Section: Discussionmentioning
confidence: 99%